Electrospun fibers based on Arabic, karaya and kondagogu gums - Padil, Vinod Vellora Thekkae; Senan, Chandra; Wacławek, Stanisław; Černík, Miroslav (International journal of biological macromolecules, 2016)
Nanofibers of natural tree polysaccharides based on three gums namely Arabic (GA), karaya (GK) and kondagogu (KG) have been prepared for the first time using electrospinning. Electrospinning solutions were prepared by mixing gum solutions of GA, GK & KG with eco-friendly polymers such as polyvinyl alcohol (PVA) or polyethylene oxide (PEO). The present study focuses on the effect of electrospinning blended solutions of GA, GK or KG with PVA or PEO, additives which influence system parameters and process parameters. This has important effects on the electrospinning process and the resulting fibers whose morphology and physicochemical properties were evaluated. The mass ratios of 70:30 to 90:10 for PVA: GA, PVA: GK and PVA: KG were observed to establish an optimum blend solution ratio in order to fabricate uniform beadless nanofibers with an average diameter of 240±50, 220±40 and 210±30nm, respectively. Various structural and physicochemical properties of the electrospun fibers were investigated. Furthermore, the comparisons of various functionalities of the untreated and plasma treated electrospun fibers were assessed. The methane plasma treated nanofibers were shown to be of extremely specific surface area, improved water contact angle, high surface porosity and roughness and superior hydrophobic properties compared to untreated fibers.
Keywords: arabská guma; Nanofibers; Tree gums; Electrospinning; plazmové plyny; nanovlákna; Plasma Gases; Karaya Gum; Gum Arabic; guma karaya; Physico-chemical properties